Retroperitoneal drainage versus no drainage after pelvic lymphadenectomy for the prevention of lymphocyst formation in patients with gynaecological malignancies. - Charoenkwan K. (2014)
BACKGROUND: Pelvic lymphadenectomy is associated with significant complications including lymphocyst formation and related morbidities. Retroperitoneal drainage using suction drains has been recommended as a method to prevent such complications. However, this policy has been challenged by the findings from recent studies. OBJECTIVES: To assess the effects of retroperitoneal drainage versus no drainage after pelvic lymphadenectomy on lymphocyst formation and related morbidities in gynaecological cancer patients. SEARCH STRATEGY: We searched the Cochrane Gynaecological Cancer Specialised Register, the Cochrane Central Register of Controlled Trials (CENTRAL, Issue 2, 2009) in The Cochrane Library, electronic databases (MEDLINE, EMBASE), and the citation lists of relevant publications. The latest searches were performed on 14 May 2009. SELECTION CRITERIA: Randomised controlled trials (RCTs) that compared the effect of retroperitoneal drainage versus no drainage after pelvic lymphadenectomy in gynaecological cancer patients. Retroperitoneal drainage was defined as placement of passive or active suction drains in pelvic retroperitoneal spaces. No drainage was defined as no placement of passive or active suction drains in pelvic retroperitoneal spaces. DATA COLLECTION AND ANALYSIS: We assessed studies using methodological quality criteria. For dichotomous data, we calculated risk ratios (RRs) and 95% confidence intervals (CIs). We examined continuous data using weighted mean difference (WMD) and 95% CI. MAIN RESULTS: Considering the short-term outcomes (within four weeks after surgery), retroperitoneal drainage was associated with a comparable rate of overall lymphocyst formation when all methods of pelvic peritoneum management were considered together (two studies, 204 patients; RR 0.76, 95% CI 0.04 to 13.35). When the pelvic peritoneum was left open, the rates of overall lymphocyst formation (one study, 110 patients; RR 2.29, 95% CI 1.38 to 3.79), and symptomatic lymphocyst formation (one study, 137 patients; RR 3.25, 95% CI 1.26 to 8.37) were higher in the drained group. At 12 months after surgery, the rates of overall lymphocyst formation were comparable between the groups (one study, 232 patients; RR 1.48, 95% CI 0.89 to 2.45). However, there was a trend toward increased risk of symptomatic lymphocyst formation in the group with drains (one study, 232 patients; RR 7.12, 95% CI 0.89 to 56.97). AUTHORS' CONCLUSIONS: Placement of retroperitoneal tube drains has no benefit in prevention of lymphocyst formation after pelvic lymphadenectomy in patients with gynaecological malignancies. When the pelvic peritoneum is left open, the tube drain placement is associated with a higher risk of short and long-term symptomatic lymphocyst formation.